Peru : Request for Arrangement Under the Flexible Credit Line-Press Release; Staff Report; and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report ;, 2020)
This paper highlights Peru's Request for Arrangement Under the Flexible Credit Line (FCL). Peru qualifies for the FCL by virtue of its very strong fundamentals and institutional policy frameworks and track record of economic performance and policy implementation. The coronavirus disease 2019 shock poses an extraordinary challenge, which is pushing the Peruvian economy into a recession. The authorities have responded decisively by putting in place stringent containment measures and a large policy package to limit the socio-economic fallout, which has been possible thanks to Peru's ample fiscal space and monetary policy credibility. The package includes a broad set of measures aimed at containing the health emergency, supporting vulnerable businesses and households, and maintaining adequate credit flows to the economy. Nonetheless, and despite its very strong policy buffers, Peru remains vulnerable to external tail risks. A prolonged Covid-19 outbreak would have significant repercussions for trade and financial flows, which could put significant pressure on Peru's balance of payments and magnify the adverse domestic impact of the coronavirus disease 2019 shock.